2018
DOI: 10.11144/javeriana.sc23-2.drio
|View full text |Cite
|
Sign up to set email alerts
|

Decreased rotavirus infection of MA104 cells via probiotic extract binding to Hsc70 and ß3 integrin receptors

Abstract: Probiotic bacteria are microorganisms beneficial to human health, useful to improving biological conditions. Thanks to probiotic bacteria the symptoms of viral infections can be alleviated. Different mechanisms whereby probiotic bacteria exert they antiviral effect have been proposed. The aim of this study was to determine whether probiotic bacteria extracts bind to receptors of host cells susceptible of rotavirus (RV) infection. To accomplish this objective, four probiotic bacterial strains of Lactobacillus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…On the other hand, herein the reduction of viral shedding exerted by Lactobacillus is in line with other studies, which found that L. rhamnosus GG was able to reduce RV elimination in gnotobiotic piglets infected with human RV [14] and in children [59]. In vitro studies have reported that Bifidobacteria and Lactobacillus are able to inhibit RV infection [2,37], for example by interfering in the adhesion step. In this regard, it may be possible that glycans or other molecules found on the surface of the bacteria interact with the virus, therefore blocking the infection, similar to oligosaccharides present in breastmilk [70,71] and infant formula [13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, herein the reduction of viral shedding exerted by Lactobacillus is in line with other studies, which found that L. rhamnosus GG was able to reduce RV elimination in gnotobiotic piglets infected with human RV [14] and in children [59]. In vitro studies have reported that Bifidobacteria and Lactobacillus are able to inhibit RV infection [2,37], for example by interfering in the adhesion step. In this regard, it may be possible that glycans or other molecules found on the surface of the bacteria interact with the virus, therefore blocking the infection, similar to oligosaccharides present in breastmilk [70,71] and infant formula [13].…”
Section: Discussionsupporting
confidence: 89%
“…Probiotics are defined as "live microorganisms that, when administered in adequate amounts, confer a health benefit on the host" [1]. Several commensal microorganisms with probiotic properties are known to reside in the gastrointestinal tract of humans as part of the microbiota [2]. In this context, probiotics are currently being used to prevent illness, improve health, and treat intestinal diseases such as infections triggered by numerous pathogens, including viruses [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that protein rich extracts of Bifidobacterium spp. interfered with rotavirus adhesion on MA104 cells by binding b3-integrins and Hsc70 [17]. In addition, Chenoll et al found that proteinaceous substance, an 11-amino acid peptide, from supernatant of B. longum CECT 7210 inhibit the replication of rotavirus [18].…”
Section: Discussionmentioning
confidence: 99%
“…and Bifidobacterium spp. with integrin (β 3 ) binding capability blocked RV infectivity at the post-attachment step ( Figure 2 ) [ 61 , 65 , 66 ]. Moreover, the strain-specific anti-RV effects of the flavonoid genistein (but not of its inactive analogue daidzein) at the virus-host cell surface attachment stage has been explained to possibly stem from inhibition of integrin activation though the protein tyrosine kinase inhibition activity of genistein [ 67 ].…”
Section: Exploiting Host Determinates To Enable Entry Of Virionsmentioning
confidence: 99%